O canto de soltura de Rhinella crucifer (Wied-Neuwied, 1821), no Estado de Pernambuco, Nordeste do Brasil - Silva, Flávio José da (2022)
In this work, we describe for the first time the release call of Rhinella crucifer in addition to comparing its advertisement call with other species of your group. The records were made in an area of Atlantic Forest, named Refúgio de Vida Silvestre Matas de Sirij, in the municipality of São Vicente Férrer, state of Pernambuco, in the Northeast Region of Brazil. At 18 June 2019, 24 advertisement vocalizations of four males were recorded, of which three emit 31 release calls. The results showed a structural difference between the two types of vocalizations, such as the presence of pulses defined, harmonics and greater modulation in the release call. Compared to other Rhinella species of the crucifer group, the release call of R. crucifer had a greater resemblance to R. ornata in the duration and interval of notes and number and interval of pulses. While the proximity of the dynamic parameters of the advertisement call with R. casconi, the highlight was the compatibility of the dominant frequency with R. inopina. This work adds new information on the vocal repertoire of the species, which contributes to information about your natural history.